The relationship between physical functional limitations, and psychological distress: Considering a possible mediating role of pain, social support and sense of mastery - Ingeborg Flåten Backe; Grete Grindal Patil; Ragnhild Bang Nes; Jocelyne Clench-Aas (Elsevier, 2018)
The aim of this study was to examine associations between selected physical functional limitations related to performing daily activities and psychological distress. We also aimed to investigate if these associations vary across age (moderation), and to explore pain, sense of mastery and social support as potential moderators and mediators. The study was based on pooled data from two rounds (2008 and 2012) of a Norwegian nationally representative cross-sectional health survey (N = 8520) including individuals aged ≥ 16 years (Age groups = 16-44 and ≥ 45 years). Physical functional limitations comprised decreased ability to: i) climb stairs, ii) carry objects, or iii) both. Psychological distress was measured as anxiety and depressive symptoms occurring separately or in combination (CAD). Of respondents reporting physical functional limitations, 8-14% reported depressive symptoms, 5-7% anxiety symptoms, and 13-28% reported CAD. Physical functional limitations were significantly associated with all three forms of psychological distress, particularly among individuals 16-44 years, and were more strongly related to CAD than to anxiety or depression occurring separately. The association with CAD was twice as strong when both types of physical functional limitations were present. Pain, sense of mastery and social support were significant modifiers of depression, whereas all three were significant mediators of the relationship between physical functional limitations and anxiety, depression and CAD. Sense of mastery mediated the relationship between physical functional limitations and CAD, but most strongly among those 16-44 years. Social support was only a significant mediator among those ≥ 45 years. Close associations between physical functional limitations and psychological distress highlight special needs among individuals experiencing daily functional limitations. The results also suggest that pain, low social support, and low sense of mastery may contribute to aggravate psychological distress. Keywords: Anxiety, Depression, Moderation analysis, Mediation analysis